2021
DOI: 10.1177/01461672211050515
|View full text |Cite
|
Sign up to set email alerts
|

Helpful or Harmful? The Role of Personality Traits in Student Experiences of the COVID-19 Crisis and School Closure

Abstract: Little is known about the individual differences in student experiences and expectations of the COVID-19 crisis and the resulting school closures. Yet, as the crisis may have uniquely impacted students, knowledge about their personalities is highly relevant. In a sample of 347 Flemish students, this study explored the association between personality traits and differences in responses to the crisis. The Big Five personality traits of students were assessed in January 2020, prior to the COVID-19 outbreak. Stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 76 publications
(120 reference statements)
2
10
0
Order By: Relevance
“…Most of existing research (Iterbeke & De Witte, 2022 ; Sahinidis & Tsaknis, 2021 ; Steinberger, 2021 ) revealed that neuroticism has a positive relationship with academic anxiety, while openness has a negative one. However, researchers obtained conflicting conclusions in other personality traits due to interindividual differences.…”
Section: Exploratory Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of existing research (Iterbeke & De Witte, 2022 ; Sahinidis & Tsaknis, 2021 ; Steinberger, 2021 ) revealed that neuroticism has a positive relationship with academic anxiety, while openness has a negative one. However, researchers obtained conflicting conclusions in other personality traits due to interindividual differences.…”
Section: Exploratory Analysis and Resultsmentioning
confidence: 99%
“…Studies have investigated the effects of personality traits on educational outcomes during the COVID-19 pandemic, with a focus on psychological factors such as class satisfaction and academic anxiety. Sahinidis and Tsaknis ( 2021 ), Iterbeke and De Witte ( 2022 ) found that openness and conscientiousness have a positive correlation with student satisfaction in synchronous online learning, while neuroticism has a negative correlation. Hong et al also found that higher levels of neuroticism result in more negative emotions during lockdowns, according to results from 273 participants (Hong, 2021 ).…”
Section: Related Workmentioning
confidence: 99%
“…Earlier higher neuroticism associated with future lower life satisfaction and positive feelings, and higher negative feelings. In contrast, positive personality traits, such as agreeableness and conscientious, explained better adjustment to the crisis (Iterbeke & De Witte, 2022).…”
Section: Introductionmentioning
confidence: 82%
“… Airaksinen et al (2021) linked personality to levels of precautions taken against COVID-19, finding that higher levels of conscientiousness, openness and neuroticism predicted precautionary health behaviours in older adults. Individuals with high levels of neuroticism have a higher likelihood of holding fears about COVID-19 than other Big 5 personalities ( Aschwanden et al, 2021 ) and experienced higher levels of stress throughout the pandemic ( Iterbeke & De Witte, 2021 ; Liu et al, 2020 ). Aschwanden et al (2021) also found that neuroticism was associated with higher levels of uncertainty during the pandemic.…”
Section: Discussionmentioning
confidence: 99%